A surprising diagnosis in a patient presenting with urticaria and uncontrolled asthma symptoms: A rare case of pleomorphic adenoma in the trachea (Annals of Medical Research, 2025)
Pleomorphic adenomas are the most common benign tumors of the salivary glands. Although they frequently occur in the parotid gland, they are rarely observed in the trachea. Diagnosis can be delayed because the symptoms may mimic those of asthma. In this case report, we present a case of pleomorphic adenoma in the trachea in a patient who had been experiencing intermittent urticaria for 2 years and had uncontrolled respiratory symptoms for the last 2 months despite clinical asthma treatment. This study aimed to raise awareness among clinicians about differential diagnoses by highlighting the absence of asthma and urticaria symptoms following tracheal lesion removal by thoracic surgery.
Keywords: Asthma; Urticaria; Pleomorphic adenoma; Trachea; Fixed obstruction